Production of lactic acid from cultivation of Rhizopus oryzae NRRL 395 and characterization of its polymer derivative / Wan Nasrin Afifa Wan Daud - Wan Daud, Wan Nasrin Afifa (2019)
In this work, the project is to discover an alternative way to substitute non-biodegradable plastic with biodegradable plastic from poly(L)-lactic acid (PLLA) polyester, using direct polycondensation (DPC) process. The first objective is to determine the growth and morphology of Rhizopus oryzae NRRL 395 and its ability to produce L-lactic acid (LLA) from microbial lactic acid fermentation (MLAF) of cassava starch. The second objective is to study the effect of spores concentration, substrate concentration, temperature and time on LLA concentration, yield and productivity in MLAF.